Fat Content, Fatty Acid Composition, and Nutritional Indices/Ratios of Balut from Itik-Pinas Mallard Ducks in the Philippines - Bondoc, O. L.; Ramos, A. R.; Santiago, R. C. (Faculty of Animal Science, Bogor Agricultural University, 2023)
Fatty acid (FA) composition is the principal measure of the nutritional quality of fats in balut (i.e., boiled fertilized eggs from mallard ducks) that may affect human cardiovascular health. This study aimed to compare the fat content, FA composition, and nutritional indices/ratios concerning the edible components of 15-day old balut (B15d) and 18-day old balut (B18d) produced by Itik Pinas duck breeds (IP-Itim, IP-Khaki, and Kayumanggi-IP– an “IP-Khaki × IP-Itim” F1 cross) in the Philippines. A total of 275 pooled samples of the embryo, yolk, albumen, and fluid portion from 154 B15d and 175 B18d balut eggs were analyzed for fat content and FA composition by gas chromatography. Fat content was highest in the yolk (29.59%), followed by the embryo (1.63%) and negligible in both albumen and fluid portions. The major FAs with the highest proportion by weight of total FAs in the solid components of balut were oleic acid C18:1n-9 (20.7%–43.8%), palmitic acid C16:0 (12.0%–24.5%), stearic acid C18:0 (2.7%–8.9%), and linoleic acid C18:2n-6 (3.5%–6.9%). The fluid portion was dominated by arachidonic acid C20:4n-6 (18.8%), trans-vaccenic acid C18:1n-7 (17.6%), oleic acid (9.0%), and palmitic acid (8.3%). Total saturated FAs (SFA) were higher in the embryo than in the yolk. However, monounsaturated FAs (MUFA) and polyunsaturated FAs (PUFA) were higher in the yolk than in the embryo. Total SFA was higher, while total MUFA and PUFA were lower in B15d balut than those in B18d balut. Since SFAs are considered unhealthy compared to MUFAs and PUFAs, the yolk from B18d balut produced by Kayumanggi-IP ducks appears to have greater health benefits due to its lower atherosclerotic and thrombotic potential and higher health-promoting index and hypocholesterolemic/ hypercholesterolemic ratio.